The EU‒NATO Cooperation after the Start of Russian Military Campaign - Alexander A. Aleshin (Современная Европа)
The EU and NATO have been developing cooperation since 2002. А new stage of cooperation between the two structures began since 2016, as a result of which their cooperation has reached a qualitatively new level. There has been formed a single transatlantic security space, in which the EU and NATO coordinate strategic goal-setting, practical policies, and activities in the field of defence and security in a number of areas. The main focus was on hybrid threats and military mobility. The start of Russian military campaign in Ukraine has become an important factor in changing the security environment in Europe and the security threats identified by the EU and NATO. The article examines the stage of EU‒NATO cooperation after February 2022. The purpose of the study is to identify trends in the development of interaction between these two structures. And first of all, determine which trend is the key: the rapprochement of the EU and NATO or the accumulation of contradictions between them. Bilateral EU‒NATO documents during the specified period were studied using the content-analysis method. It was revealed that since 2022, EU‒NATO cooperation did not move to a qualitatively new level and developed in accordance with the trends of the previous period. This is reflected in the absence of fundamentally new areas of bilateral interaction and new joint projects. The reasons for this are the existing contradictions between the two structures, studied in the article. At the same time, it was noted that despite the contradictions, there is a continuation of the development of a single transatlantic security space, due to the further division of responsibilities between the EU and NATO, their cooperation in areas of common interests and the increasing role of the US and NATO. This occurs in the context of identifying direct threats from third states (Russia and partly China).